IMPACT OF COVID-19 ON EDUCATION IN INDIA - Manju Dhillon, Anviti Rawat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The virus that is called as Coronavirus now days, has started in Wuhan (China) and it has spread to develop and developing countries very fast. The coronavirus has created greatest impact on the developed countries like America, Italy and France. Due to the coronavirus the countries has to implement the Lockdown. The lockdown phase has created major Impact on the education system, the traditional education that we generally use that is now completely shut down. This study aims to assess the impact of lockdown on education system in India. The study also include various Initiatives taken by Govt. of India for education system during this pandemic.